Incidence of delirium following hospitalization of elderly people with fractures: risk factors and mortality - Brunna Rodrigues de Lima; Brenda Kelly Gonçalves Nunes; Lara Cristina da Cunha Guimarães; Lucenda Fellipe de Almeida; Valéria Pagotto (SciELO, 2021)
ABSTRACT Objective: To identify the incidence, risk factors for delirium, and its association with death in the elderly hospitalized with fractures. Method: Prospective cohort, with a one-year follow-up of elderly people with clinical or radiological diagnosis of fracture, from an emergency and trauma hospital in the state of Goiás. The outcome delirium was defined by the medical description in the medical record. The predictor variables were demographic, health conditions, and hospitalization complications. A hierarchical multiple analysis was performed using robust Poisson regression, with Relative Risk as a measure of effect. Results: A total of 376 elderly patients were included. The incidence of delirium was 12.8% (n = 48). Risk factors were male gender, age ≥80 years, dementia, heart disease, osteoporosis, chronic obstructive pulmonary disease, high-energy traumas, pneumonia, urinary tract infection, and surgery. The risk of death in the sample was 1.97 times higher (HR: 1.97 95% CI 1.19-3.25) in elderly people with delirium. Conclusion: Delirium had an intermediate incidence (12.8%); the risk of death in this group was about 2 times higher in one year after hospital admission. Demographic factors, past history of diseases, surgery, and complications have increased the risk and require monitoring during hospitalization of elderly people with fractures.